Electrophoretic and chemical characterization of lipopolysaccharides of Vibrio parahaemolyticus. - Han, T J (1992)
Lipopolysaccharides (LPSs) isolated from three Kanagawa-positive and three negative strains of Vibrio parahaemolyticus were characterized by using electrophoretic, immunochemical, and chemical methods. The results of this study indicated that the LPSs of all six strains of V. parahaemolyticus examined did not have an O-specific side chain. These V. parahaemolyticus LPSs appeared to have molecular weights similar to that of the rough-type (Ra) LPS of Salmonella typhimurium TV-119 and might just contain lipid A and a core region. However, the microheterogeneity of V. parahaemolyticus LPS observed was greater than that of S. typhimurium LPS. The profile of V. parahaemolyticus LPS consisted of closely spaced triplet or quadruplet bands, but that of S. typhimurium consisted of doublet bands. Slower-moving bands appeared on sodium dodecyl sulfate-polyacrylamide gel electrophoresis gels only when large amounts of V. parahaemolyticus LPS were loaded. These bands were proven to be the aggregates of the fastest-moving low-molecular-weight bands by re-electrophoresis. The banding pattern of V. parahaemolyticus LPSs produced on nitrocellulose membranes by immunoblotting indicated that the V. parahaemolyticus LPSs did not have an O-specific side chain. The low ratio of total carbohydrate to lipid A of V. parahaemolyticus LPSs also suggested that they were like rough-type LPS. The mobility and profile of V. parahaemolyticus LPS on sodium dodecyl sulfate-polyacrylamide gel electrophoresis gel and its chemical composition were closely related to the serotype of a specific strain but not with the Kanagawa phenomenon.